Exploring Psychological Safety in Software Engineering: Insights from Stack Exchange - Santana, Beatriz Silva De; Freire, Sávio; Cruz, Leandro; Monte, Lidivânio; Mendonca, Manoel; Santos, José Amancio Macedo (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2023)
[Context] Interpersonal relationships are as important as processes and technology mastery in software engineering. These relationships can impact the quality of the software product and the software teams’ quality of life. Understanding how and which aspects impact interpersonal relationships is essential for a psychologically safe environment. However, little is known about which aspects may affect the maintenance of a psychologically safe environment within the software engineering context. [Aims] This study aims to investigate interpersonal conflict scenarios and their potential indicators of psychological insecurity from the perspective of software practitioners. [Method] This article identified and qualitatively analyzed discussions related to psychological safety on Stack Exchange, an important question-and-answer site used by software professionals in their daily activities. [Results] We identified 11 scenarios concentrated on four types of interpersonal relationships: with the client, with team members, with leadership, and with other departments. In addition, we investigated whether there were previous attempts to resolve conflicts. Lastly, we found seven potential indicators of psychological insecurity in the conflicts exposed. [Conclusion] We organized the set of scenarios and their potential indicators of psychological insecurity in a Sankey diagram. It can support researchers and practitioners in understanding how to define a healthier and more productive environment for software projects.